THE FORMATION OF SUBMARINE BARUNA KOMBA RIDGE ON NORTHEAST FLORES WATERS IN RELATION TO LOW ANOMALY OF MARINE MAGNETISM - Lili Sarmili; Mustaba Ari Suyoko (BULLETIN OF THE MARINE GEOLOGY, 2012)
There are three submarine ridges found on northeast of Flores waters. One of them is Baruna Komba submarine ridge found on south of Komba (Batutara) Volcano. Two others are Abang and Ibu Komba volcanoes located more to the southeast of the Baruna Komba. The position of the Baruna Komba situated more closely to the active Komba volcano and it is considered that the formation of Baruna Komba ridge is younger than the Abang and Ibu Komba volcanoes. The Baruna Komba also interpreted before as a magmatic volcano. Data from marine magnetism shows that there is a low or negative anomaly on Baruna Komba ridge whereas on Abang and Ibu Komba ridges, they are high and positive anomalies. These data indicate that the Baruna Komba ridge is not a volcanic ridge but it is a submarine ridge formed by a volcanic detritus or non magnetized sedimentation. The low anomaly around these submarine ridges gives northwest to southeast lineation and we interpreted also as a big fault on the west side of these ridges. On the other hand, the Abang and the Ibu Komba ridges are closely related to submarine magmatic volcanoes. Keywords : The Baruna Komba, magmatic volcano, volcanic detritus, Northeast Flores Waters. Di perairan sebelah timur laut pulau Flores ditemukan tiga bukit bawah laut. Salah satunya adalah Baruna Komba sebagai bukit bawah laut yang ditemukan di selatan gunung api Komba. Dua bukit lainnya adalah Abang dan Ibu Komba di sebelah tenggara Baruna Komba. Posisi Baruna Komba terletak lebih dekat dengan gunung api Komba yang masih aktif sehingga ditafsirkan sebagai bukit bawah laut termuda dibandingkan gunung api bawah laut Abang dan Ibu Komba. Baruna Komba ditafsirkan sebelumnya sebagai gunung api juga. Dari data magnetik kelautan menunjukkan bahwa adanya anomali negatif atau rendah di atas Baruna Komba, sedangkan di atas Abang dan Ibu Komba menunjukkan anomali positif atau tinggi. Data magnetik ini menandakan bahwa bukit bawah laut Baruna Komba bukan sebagai gunung api tetapi terbentuk oleh material seperti lava, breksi gunung api dan lahar yang terendapkan sewaktu letusan gunung api Komba. Sebaliknya, bukit bawah laut Abang dan Ibu Komba dapat ditafsirkan sebagai gunung api bawah laut yang bersifat magmatik. Kata Kunci : Baruna Komba, gunung api bersifat magmatik, endapan vulkanik, perairan timur laut Flores.